Bifunctional NiFe LDH as a piezoelectric nanogenerator and asymmetric pseudo-supercapacitor. (21st July 2022) - Veeralingam, Sushmitha; Gunasekaran, Sivagaami Sundari; Badhulika, Sushmee
Abstract : Lead-free nickel–iron layered-double hydroxide (NiFe LDH) nanomaterial is used to fabricate a self-powered unit based on a piezoelectric nanogenerator and high-performance asymmetric supercapacitor (ASC). Abstract : Herein, a lead-free nickel–iron layered-double hydroxide (NiFe LDH)-based piezoelectric nanomaterial is used to fabricate a self-powered unit based on a piezoelectric nanogenerator and high-performance asymmetric supercapacitor (ASC). XRD analysis of the NiFe LDH nanostructure confirms the distortion of the octahedral structural of (Ni, Fe)(OH) 2+ cationic layers with respect to anionic layers of (CO3 ) 2−, which is responsible for the piezoelectric effect in the NiFe LDH nanostructures. A piezoelectric force microscope (PFM) study of the NiFe LDH nanostructure is performed and a superior piezoelectric charge coefficient of 274 pm V −1 is obtained. A flexible, semi-transparent NiFe LDH:PDMS-based piezoelectric nanogenerator is fabricated with the device configuration of Pt-coated PET/(NiFe LDH:PDMS)/ITO-coated PET. A peak output voltage was obtained as 53 V and a peak current density was obtained as 0.79 μA cm −2 under a compression force of 0.15 kgf. The high value of the piezoelectric charge coefficient of the NiFe LDH and the low surface energy of the PDMS polymer is accountable for the generation of this high output. The NiFe LDH:PDMS-based piezoelectric nanogenerator (PENG) possesses a high energy-conversion efficiency of 34 ± 0.2% with a fast response time of 40 ms. Furthermore, to explore the practical utility of the nanogenerator, an asymmetric supercapacitor using the as-prepared NiFe LDH and biomass-derived activated carbon (AC) as the positive and negative electrode, respectively, is fabricated resulting in a capacitance of 1340 F g −1 at 1 A g −1 . The supercapacitor is charged using the NiFe LDH nanogenerator and an efficient charging curve of up to 0.8 V·s is observed under continuous tapping for 100 s. The integrated self-powered system that works by charging the ASC using a piezoelectric hybrid nanogenerator is demonstrated, which provides a promising direction in powering smart wearable electronic devices.